Communication centers and oral communication programs in higher education advantages, challenges, and new directions - Yook, Eunkyong Lee; Atkins-Sayre, Wendy, 1972- (Lexington Books, 2012)
"Communication Centers and Oral Communication Programs in Higher Education, edited by Eunkyong L. Yook and Wendy Atkins-Sayre reveals vital information that is of theoretical and practical importance to higher education administrators, educators, and communication centers directors and staff. It is the first book to be published on communication centers"-- Provided by publisher.